Antidepressant-Like Activity and Physicochemical Analysis of Essential Oils from Michelia alba and Plumeria alba Flowers - Nayaka, Ni Made Dwi Mara Widyani; Swari, Ni Luh Putu; Widnyani, Dewa Ayu Sri Bintang; Sukmayanti, Ni Kadek; Yuda, Putu Era Sandhi Kusuma; Wardani, I Gusti Ayu Agung Kusuma; Sanjaya, Dwi Arymbhi (JST (Jurnal Sains dan Teknologi), 2022)
Depression is a mental disorder with an increased prevalence. Other than conventional antidepressants, essential oils have been used in aromatherapy as a complementary and alternative medicine to reduce depression. In the current study, the antidepressant-like activity of the inhalation of essential oils from Michelia alba (MAEO) and Plumeria alba (PAEO) flowers was analyzed using the forced swim test. The immobility time of mice from tested groups was evaluated statistically by the non-parametric Kruskal Wallis test, followed by the Mann Whitney post hoc test. Also, the characterization of both essential oils was determined by refractive index, solubility, and Gas Chromatography-Mass Spectrophotometry (GC-MS) analysis. PAEO showed stronger antidepressant-like activity than MAEO (p<0.05) and it was equal to the positive control (essential oil of Lavandula angustifolia) (p>0.05). The GC-MS analysis revealed some calming agents in MAEO and PAEO such as linalool, linalyl acetate, phenylethyl alcohol, and methyl anthranilate.